Schistosoma japonicum HSP60-derived peptide SJMHE1 suppresses delayed-type hypersensitivity in a murine model - Wang, Xuefeng (Parasit Vectors, 2016)
BACKGROUND: Parasite-derived molecules with immunomodulatory properties, which have been optimised during host-parasite co-evolution, exhibit potential applications as novel immunotherapeutics. We have previously demonstrated that Schistosoma japonicum HSP60-derived peptide SJMHE1 induces CD4(+)CD25(+) regulatory T-cells (Tregs) and that adoptively transferred SJMHE1-induced CD4(+)CD25(+) Tregs inhibit delayed-type hypersensitivity (DTH) in mice. However, multiple concerns regarding this method render this treatment unsuitable. To gain further insights into the potential effects of SJMHE1, we used ovalbumin (OVA)-induced DTH and evaluated the effect of SJMHE1 on DTH mice. METHODS: BALB/c mice were sensitised with OVA alone or combined with SJMHE1 and then challenged with OVA to induce DTH. We first analysed the potential effects of SJMHE1 by measuring DTH responses, T-cell responses, cytokine secretion, and Treg proportions. We then evaluated the expression levels of IL-10 and TGF-β1 in CD4(+)CD25(+) T-cells during DTH and Treg generation to identify the mechanism by which SJMHE1 suppresses DTH. RESULTS: SJMHE1 modulated the effector response against OVA-induced DTH and stimulated the production of the anti-inflammatory cytokines IL-10 and TGF-β1 in immunised mice through a mechanism involving CD4(+)CD25(+) Tregs. SJMHE1-induced CD4(+)CD25(+) Tregs expressed high levels of CTLA-4, IL-10, and TGF-β1, which substantially contributed to the suppressive activity during DTH. The administration of SJMHE1 to DTH in mice led to the expansion of CD4(+)CD25(+) Tregs from CD4(+)CD25(−) T-cells in the periphery, which inhibited DTH responses. CONCLUSIONS: Our study proves that the parasite-driven peptide suppresses DTH in mice, which may confer a new option for inflammation treatment.